The Dual Role of HLA-C in Tolerance and Immunity at the Maternal-Fetal Interface - Papúchová, Henrieta; Meissner, Torsten B.; Li, Qin; Strominger, Jack L.; Tilburgs, Tamara (Frontiers in Immunology, 2019)
To establish a healthy pregnancy, maternal immune cells must tolerate fetal allo-antigens and remain competent to respond to infections both systemically and in placental tissues. Extravillous trophoblasts (EVT) are the most invasive cells of extra-embryonic origin to invade uterine tissues and express polymorphic Human Leucocyte Antigen-C (HLA-C) of both maternal and paternal origin. Thus, HLA-C is a key molecule that can elicit allogeneic immune responses by maternal T and NK cells and for which maternal-fetal immune tolerance needs to be established. HLA-C is also the only classical MHC molecule expressed by EVT that can present a wide variety of peptides to maternal memory T cells and establish protective immunity. The expression of paternal HLA-C by EVT provides a target for maternal NK and T cells, whereas HLA-C expression levels may influence how this response is shaped. This dual function of HLA-C requires tight transcriptional regulation of its expression to balance induction of tolerance and immunity. Here, we critically review new insights into: i) the mechanisms controlling expression of HLA-C by EVT, ii) the mechanisms by which decidual NK cells, effector T cells and regulatory T cells recognize HLA-C allo-antigens, and iii) immune recognition of pathogen derived antigens in context of HLA-C.